2018
DOI: 10.1080/00222895.2018.1468312
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Attentional Focus on Balance Control over Seven Days of Training

Abstract: This study examined the training effect of attentional focus (external focus, internal focus, or no focus instructions) on a dynamic balance task. Participants completed baseline balance testing, seven consecutive days of dynamic balance board training, and retention testing 24 hours after the last session. The novel finding of this study was the presence of a training effect on balance control when adopting an external focus relative to an internal focus or no focus instructions. Further, we report the unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 74 publications
3
14
0
Order By: Relevance
“…Implicit learning contributes to reorganization of the motor cortex, (Hirano, Kubota, Koizume, Tanaka, & Funase, ) highlighting potential strategies to leverage neuroplasticity. For instance, supplementing ACL injury prevention methods with an external focus (i.e., verbal instruction that directs attention toward the effects of one's movement Diekfuss, Rhea, et al, ; Wulf, ; Wulf, Höß, & Prinz, )) and/or integrating analogies (i.e., verbal instruction utilizing metaphors (Liao & Masters, )) may enhance functional connectivity through synaptogenic processes (Wulf & Lewthwaite, ). Indeed, recent evidence indicates that adopting such motor learning techniques does in fact influence brain activity (Raisbeck, Diekfuss, Grooms, & Schmitz, ; Sakurada, Hirai, & Watanabe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Implicit learning contributes to reorganization of the motor cortex, (Hirano, Kubota, Koizume, Tanaka, & Funase, ) highlighting potential strategies to leverage neuroplasticity. For instance, supplementing ACL injury prevention methods with an external focus (i.e., verbal instruction that directs attention toward the effects of one's movement Diekfuss, Rhea, et al, ; Wulf, ; Wulf, Höß, & Prinz, )) and/or integrating analogies (i.e., verbal instruction utilizing metaphors (Liao & Masters, )) may enhance functional connectivity through synaptogenic processes (Wulf & Lewthwaite, ). Indeed, recent evidence indicates that adopting such motor learning techniques does in fact influence brain activity (Raisbeck, Diekfuss, Grooms, & Schmitz, ; Sakurada, Hirai, & Watanabe, ).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the external visual focus of attention leads to better motion stability than the internal visual focus of attention. Some studies have shown that the external visual focus of attention can enhance the balance of exercise [32]. Wulf et al [33] considered that subjects' motions had higher frequency adjustments in an external focus of attention.…”
Section: Discussionmentioning
confidence: 99%
“…An external focus has robustly demonstrated enhanced performance and/or learning in numerous motor tasks including balance control [57,60,118,164,187,246], basketball free throw shooting [6], discus throwing [249], reaction and movement preparation time [113], sprint speed [98], and jump/hop distance [174,175,182,232]. More specifically, an external focus has resulted in more effective (e.g.…”
Section: Pillar 3: An External Focus Of Attentionmentioning
confidence: 99%